1948
DOI: 10.1002/jctb.5000670804
|View full text |Cite
|
Sign up to set email alerts
|

A study of some chemical reactions employed in photometric analysis

Abstract: The paper describes an investigation into a number of the chemical reactions employed in photometric analysis for the determination of silicon, manganese, chromium, nickel, vanadium, titanium, copper, iron and molybdenum. The influence of a large number of variables has been studied in order to establish the optimum solution conditions for the development of stable and reproducible colours irrespective of the class of material in which the clement to be determined may occur.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1950
1950
1985
1985

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…2 The color of the residue results from traces of other metals. 3 Experiments showed that any V that may be present is not dissolved by the NH3. 4 If the NaOH is made in a polyethylene rather than a glass bottle, no silica or other metals are introduced from the glass.…”
Section: Hno3 a White Curdy Precipitate Indicates Agmentioning
confidence: 99%
“…2 The color of the residue results from traces of other metals. 3 Experiments showed that any V that may be present is not dissolved by the NH3. 4 If the NaOH is made in a polyethylene rather than a glass bottle, no silica or other metals are introduced from the glass.…”
Section: Hno3 a White Curdy Precipitate Indicates Agmentioning
confidence: 99%
“…( 4) Mitchell, R. L., "Spectrographie Analysis of Soils, Plants and Related Materials," Harpenden, England, Commonwealth THE only known color reaction suitable for the spectrophotometric determination of silicon is based on its reaction with molybdic acid to form molybdisilicic acid. The yellow color of this acid is the basis for much of the early work (2,12,18,24,25) and for the determination of silicon in steels (15). Reduction of the molybdisilicic acid to a heteropoly blue complex ion by various reducing agents (8, 4,6,13,20,22,23,27,28,SO) increases the sensitivity of the method.…”
Section: Literature Citedmentioning
confidence: 99%
“…A new standard reference curve should be established about every 2 years or whenever a new batch of solid diphenylcarbazide is used (cf. 10).…”
Section: Standardizationmentioning
confidence: 99%
“…Although a slight discoloration does not interfere with the determination, a fresh reagent was prepared as soon as a discoloration became apparent. The solid diphenylcarbazide is also kept in a refrigerator in order to retard deterioration (10). As shown in Figure 3, the concentration of the reagent in the final solution has a definite influence upon the time needed for the development of the maximal color.…”
Section: S-diphenylcarbazide Compoundmentioning
confidence: 99%